PENGGUNAAN CANVA DIGITAL MARKETING BAGI WANITA UMKM SINDANG JAYA TANGERANG - Setyawan, Ignatius Roni; Listyarti, Indra; Amerta Mardjono; Valentina Carolina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The results of the evaluation of the 2022-2024 PKM activities and the results of discussions and sharing with the sub-district and the head of Forsamik (Micro and Medium Enterprises Forum) in 2022-2024, it was found that there are still many MSME actors who have not intensively used digital marketing media in promoting their products. They still do not understand how to use digital marketing in order to promote products, expand their product marketing areas, open more interactions with potential customers in each marketplace and increase their sales turnover quickly. This greatly motivated the PKM team to carry out activities again on the topic of implementing digital marketing through the Canva application for MSME actors in Sindang Jaya District. The activity was carried out in Sindang Jaya District on May 22, 2025 offline. The PKM team carried out PKM activities on the implementation of digital marketing through the Canva application in two sessions. The first session was in the form of providing comprehensive material & updates on digital marketing through the Canva application for MSMEs, and the second session was the implementation of digital marketing through comprehensive assistance on creating product designs in applications using the Canva application. The final result achieved was that almost all women UMKM were able to use the Canva digital marketing application in the form of a pamphlet. This result is a form of positive behavioral change in female UMKM participants who previously did not understand Canva digital marketing before the PKM agenda were able to prove their abilities through examples of designs for each product through the Canva application. ABSTRAK Hasil evaluasi kegiatan PKM 2022-2024 serta hasil diskusi dan sharing dengan pihak kecamatan serta ketua Forsamik (Forum Usaha Mikro Menengah) pada tahun 2022-2024, maka diperoleh hasil bahwa masih banyak para pelaku UMKM yang belum intens menggunakan sarana pemasaran digital dalam mempromosikan produknya. Mereka masih belum memahami cara penggunaan pemasaran digital dalam rangka mempromosikan produk, memperluas daerah pemasaran produknya, membuka lebih banyak interaksi dengan pelanggan potensial dalam setiap marketplace dan menaikkan omzet penjualannya dengan cepat. Hal ini sangat memotivasi tim PKM melakukan kegiatan kembali dalam topik impkementasi pmasaran digital melalui aplikasi Canva kepada pelaku UMKM di Kec. Sindang Jaya. Kegiatan dilakukan di Kecamatan Sindang Jaya tanggal 22 Mei 2025 secara luring. Tim PKM melakukan kegiatan PKM tentang impkementasi pemasaran digital melalui aplikasi Canva dalam dua sesi. Sesi pertama berupa pemberian materi komprehensif & update tentang pemasaran digital melalui aplikasi Canva bagi UMKM, dan sesi kedua impelementasi pemasaran digital melalui pendampingan secara komprehensif tentang pembuatan desain produk dalam aplikasi menggunakan aplikasi Canva. Hasil akhir yang dicapai adalah hampir semua wanita UMKM mampu menggunakan aplikasi Canva digital marketing dengan dalam bentuk pamflet. Hasil tersebut merupakan bentuk perubahan perilaku positif peserta wanita UMKM yang tadinya sebelum agenda PKM belum memahami Canva digital marketing menjadi dapat membuktikan kemampuannya lewat contoh-contoh desain setiap produk melalui aplikasi Canva.